Valorization of marine-based gelatine in food product development - Carvalho, Maria Teresa Dias (2022)
This research work was conducted with the purpose of studying alternative applications of fish canning by-products, to obtain alternative added-value food products. One of today's leading trends in food product development is the design of products with enhanced nutritional profile and a sustainable ethos. In this regard, marine gelatines extracted from either yellowfin tuna (Thunnus albacares) or from blue shark (Prionace glauca) skins were studied as ingredients to develop new foods that proactively integrate scientific trends in nutrition and sustainability. Hence, the role of tuna gelatine as a fat replacer in mascarpone cheese and in tuna pâté was assessed. In the latter product, its properties as a texturizing agent were also tested. The incorporation of blue shark gelatine was not very appealing for these matrices, regardless of the tested concentration level. Due to its characteristics, that type of gelatine is more suitable for consistent products, such as jelly gums. Two sets of experimental pâté samples were prepared by: i) replacing part of oil by gelatine according to the following weight proportion oil:gelatine combinations 15:25, 10:25 and 5:35 (g/100g) and gelatine replaced cornstarch; or ii) gelatine replaced 50% cornstarch (sample A 60:10:20:10) or 50% cornstarch and decrease oil percentual content (sample B 60:10:15:15; sample C 60:10:10:20 and sample D 60:10:5:25 %(w/w) for tuna:cornstarch:oil:gelatine respectively). Prepared pâtés, in duplicate, were stored in thermally treated glass bottles and stored for 28 days at room temperature. Physical (texture and colour) and chemical (protein, fat, pH, water activity and moisture) properties of developed pâtés were assayed. Tests of sensory acceptance and sensory attributes were performed on selected formulations and microbiological stability was monitored. With the inclusion of tuna gelatine in the two types of pâté, it was possible to reduce in two thirds fat content. Samples without cornstarch showed a reduction in fat content around 67% in both days. Samples with cornstach showed differences in fat content when compared with the control sample (sample A). Samples with high gelatine content reduced the fat content more than 70% at day 0 and around 65% at day 28. Concerning mascarpone cheese, six different samples of mascarpone cheese were prepared. The two fish gelatines were tested as partial fat replacers, at two different percentages: 15% and 25%; a commercial product was included for comparative purposes. For both marine species, results showed reduced fat content, when compared to the control. Fat results showed a mean variation between 22% to 25%. The samples with yellowfin tuna gelatine had similar rheological and textural properties, when compared with control and commercial product. However, mascarpone cheese with blue shark gelatine had less softness. Colour was not affected by the inclusion of gelatine. In general, the addition of 15% gelatine presented a strong similarity in protein and fat content to the commercial sample. From sensorial and nutritional perspectives, the sample which showed best results was the one with 15% tuna gelatine. Therefore, this study shows that marine gelatine, particularly tuna gelatine, has the potential to be used as a fat replacer in mascarpone cheese production and in tuna pâtés, which could offer a value-added product in terms of health and sustainability. Este trabalho de investigação foi realizado com o intuito de valorizar os subprodutos oriundos da atividade pesqueira e obterem-se produtos alimentares com valor acrescentado de mercado. Uma das principais tendências é o desenvolvimento de alimentos com melhor perfil nutricional e carácter sustentável. Assim, foram utilizadas gelatinas de origem marinha extraídas de peles de atum (Yellowfin tuna) e tintureira (Prionace glauca).